STUDI KEANEKARAGAMAN SATWALIAR DI AREAL KONSERVASI PT. PERTAMINA TALISMAN JAMBI MERANG - Harnios Arief; Ainur Rahman; Joko Mijiarto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Gading Gas Plant Island (Joint Operationing Body Pertamina - Talisman Jambi Merang) has degradation peat swamp ecosystem because of people activity. That degradation ecosystem can disturbed the wild animal in that place. According to that, this activity have a purposed to identified the wild animal in Pertamina Talisman Jambi Merang Area. The observation held from October 2014 until January 2015, with combination point abundance method and strip transect method. The wild animal whose found in the area is 99 species of bird (three species are vulnerable IUCN, 11 species are Appendiks II CITES, 28 species are protected by PP No.7 1999), 25 species of mammal (one species is vulnerable IUCN, two species are Appendiks I CITES, four species are Appendiks II CITES, eight species are protected by PP No.7 1999), and 13 species of reptile (two species are Appendiks I CITES, five species are protected by PP No.7 1999). Keywords: Degradation, Diversity, Gading Gas Plant Island, Peat Swamp, Wildlife